EXAMEN ESPECIAL AL COMPONENTE DE INVERSIONES EN BIENES DE LARGA DURACIÓN DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DE PIÑAS, PERÍODO 2014 - GARCÍA AGUILAR, YESSENIA ESTEFANÍA (2016)
The thesis entitled "SPECIAL EXAMINATION COMPONENT OF INVESTMENTS IN LONG-TERM ASSETS DECENTRALIZED AUTONOMOUS MUNICIPAL GOVERNMENT PIÑAS, PERIOD 2014"; It was carried out through the application of various techniques and procedures, in order to evaluate the management and control of assets in compliance with the existing legal and regulatory framework. For compliance with the following specific objectives: Check the documentation to support and validate transactions related to the item to be examined, and the existence of clear and defined policies for the efficient control of goods which is responsible for the entity itself which were met through the use of methods and techniques that allowed carrying out the special examination process, structured as three phases: planning which in turn is divided into preliminary where the guide was applied prior visit In order to know general information about the company and the principal activities and specific in the evaluation matrix and risk rating to define the significance of the component it is applied; execution followed that through the implementation of programs, questionnaires and evaluation of internal control findings determined is given, which are summarized in narrative, summary and analytical cedulas; thus achieving gain evidence sufficient to carry out the last phase is the communication of results which is identified 5 by the drafting of the report containing comments, conclusions and recommendations. The second objective was aimed at assessing compliance with laws, regulations and other applicable rules in order to verify ownership, veracity and legality of transactions for the period under review, for it was taken as regards the Internal Control Standards, Budget standards, Government Accounting Standards, and other laws and regulations. To meet the third objective, we proceeded to prepare a final report with the results of the special examination applied and suggest recommendations to the relevant administrative staff, to help improve the situations encountered, such as: the obsolescence of inventories of durable goods by not performed regular physical findings, as well as the existence of goods which were already obsolete and that should have been discharged, the lack of encoding location and identification difficult, and the lack of clear and detailed records of the entry and exit of vehicles; This report is the final product of the auditor's work, and will be the benchmark for GAD authorities make the best decisions.